Cell repair: Revisiting the patch hypothesis - Davenport, Nicholas R. (Taylor & Francis, 2016)
Plasma membrane damage elicits a complex and dynamic cellular response. A vital component of this response, membrane resealing, is thought to arise from fusion of intracellular membranous compartments to form a temporary, impermeant patch at the site of damage; however, this hypothesis has been difficult to confirm visually. By utilizing advanced microscopy technologies with high spatiotemporal resolution in wounded Xenopus laevis oocytes, we provide the first direct visualization of the membrane fusion events predicted by the patch hypothesis; we show the barrier formed by patching is capable of abating exchange of material across the plasma membrane within seconds. Profound changes also occur to the plasma membrane surrounding wounds; lipid remodeling is accompanied by membrane fusion events, both conventional (e.g., exocytosis) and novel (e.g., “explodosis”). Further, we reveal additional complexity in wound-induced subcellular patterning, supporting existing evidence that extensive interactions between lipid, protein, and ionic signaling pathways shape the cellular wound response.